Effect of Visual Evoked Potentials in Patients with Primary Hypertension: Life Sciences-Physiology - Joseph, Jalsi; Joseph, Danti; Bennet, Abraham Sam Jefferson (International Journal of Life Science and Pharma Research, 2022)
Hypertension can cause vascular endothelial changes which can lead to hyalinization and demyelination. It also causes hypertensive retinopathy and retinal artery atrophy in chronic hypertensive patients. Retinal artery atrophy can lead to demyelination changes in the optic nerve. Visual evoked potentials (VEPs) can be used as a sensitive method for documenting the abnormalities in the visual pathways. VEPs are electrical potential differences recorded from the scalp to the visual stimuli. The demyelination changes of optic nerve in early stages of primary hypertension were not studied much. Hence, this study was aimed to assess the effect of VEP in primary hypertension. The main objective of this study was to correlate the latency and amplitude of VEPs in normal individuals and primary hypertensive patients. This is a comparative study which was done between two groups. Group A was a control group with 60 normal participants and group B was a study group that had 60 primary hypertensive patients. Pattern reversal VEP (Parameters – N75, P100 & N145 latencies and amplitude of P100) was recorded in both groups. The variables were correlated between group A and group B. In the result of this study, the VEP latencies of N75 and P100 waves was increased (duration delayed) significantly in both right eye and left eye of participants in Group B than Group A. Amplitude of P100 wave was decreased in both eye, but it is not statistically significant in left eye. VEP parameters can be used for routine screening and diagnostic tests for visual impairment and hypertensive retinopathy even in earlier stages of hypertensive patients.